Students perception on the use of video in learning about reproductive system - Ruqiah Ganda Putri Panjaitan; Titin Titin; Yohanes Gatot Sutapa Yuliana; Galih Albarra Shidiq (Universitas Ahmad Dahlan, 2020)
One of the variations that can be implemented in biology learning is the use of media that functions as a teaching aid in the process of delivering materials and knowledge to students. This study used reproductive system which is considered as one of the compulsory materials in an attempt to improve students awareness so that risky behaviors causing reproductive disorders can be prevented. The study aims to describe the perception of students in Pontianak on the use of video on the material about reproductive system. The type of the study was quantitative using survey as the research method. The research subjects consisted of 291 grade XI high school students from nine high schools in Pontianak. The research instrument used was a closed response questionnaire with five criteria, constructed into two aspects, clarity and impact on leaner. The analysis of the questionnaire indicated that students showed a positive response on the use of video in learning about reproductive system (74.16%), with response to the clarity aspect reaching an average of 74.71% (positive category) and the impact on leaner aspect reaching an average of 73.61%. It can be concluded that the students respond positively on the use of video as a media to learn about reproductive system.